Effects of self-efficacy on frontal midline theta power and golf putting performance - Yu, Chien-Lin; Kao, Cheng-Wei; Wu, Jia-Hao; Hung, Eric; Chang, Wei-Chun; Yang, Ren-Ting; Wang, Kuo-Pin; Hung, Tsung-Min (Frontiers in Psychology, 2024)
Introduction Self-efficacy (SE), defined as an individual's belief in their ability to complete a task, is linked to top-down attentional control, influencing motor performance in sports. Although the behavioral effects of SE are well-documented, there is a lack of research on the mechanisms through which SE affects sports performance. Our research aims to elucidate the neurophysiological mechanisms that underlie the impact of self-efficacy on sports performance. Specifically, we intend to explore the effects of low and high SE on frontal midline theta (Fmθ) activity, associated with sustained top-down attention, and on motor performance. Methods We recruited thirty-four professional golfers to perform 60 putts, during which their electroencephalographic activity was monitored. SE levels were assessed using a visual analog scale from 0 to 10 before each putt, with scores categorized into higher or lower SE based on each golfer's individual average score. Results Paired t-tests indicated that trials with higher SE scores had a higher putting success rate than those with lower SE scores (53.3% vs. 46.7%). Furthermore, trials associated with higher SE scores exhibited lower Fmθ activity compared to those with lower SE scores (4.49 vs. 5.18). Discussion Our results suggest that higher SE is associated with reduced top-down attentional control, leading to improved putting performance. These findings support Bandura's theory of SE, which suggests that the effects of efficacy beliefs are mediated by cognitive, motivational, emotional, and decision-making processes. This study sheds light on the intermediate processes of SE by examining its impact on the anticipation of outcomes, sports performance, and attentional control prior to putting.